Increased maternal mortality during the SARS-CoV-2 pandemic in Peru. A systematic review. - Flores Limo, Gloria Yesenia (2024)
Introduction: The present study explored maternal mortality during the COVID-19 pandemic, with a specific focus on pregnant women with COVID-19. Material and methods: After registration of the research protocol in PROSPERO (CRD42024506108), a review of studies during the period January 2020 to December 2023 was conducted in PubMed, Scopus, Ovid, Web of Science, Google Scholar, Virtual Health Library, and Scielo databases using an advanced search and using terms such as ['COVID-19' AND ('pregnancy' OR 'pregnant') AND (Peru)]. Studies reporting maternal mortality due to COVID-19 were included. In addition, the results were compared with epidemiological reports proposed by the Peruvian Ministry of Health (MINSA). Results: Six studies with 44 pregnant women who died from COVID-19 were included. The studies covered four regions of Peru (Lima, Cajamarca, Huancayo, and Callao). Significant maternal complications were observed, including pre-eclampsia, eclampsia, prematurity, intrauterine growth restriction, and fetal death. Among the most frequent comorbidities were hypertension, diabetes, and obesity. According to MINSA epidemiological data, a total of 1,486 pregnant women were reported to have died between 2020 and 2023. Of these, 15.1% (n = 224) of deaths were directly attributed to COVID-19. Conclusions: COVID-19 represents a significant risk for pregnant women in Peru, with deaths attributed to the disease and severe maternal complications such as pre-eclampsia and prematurity, highlighting the need for maternal health care during the pandemic. It is essential that health authorities protect pregnant women from COVID-19 through vaccination, education on preventive measures, and specialized monitoring, especially for those with comorbidities.